ประสบการณ์ชีวิตของวัยรุ่นที่ไม่เสพยาบ้าซ้ำ - ณิชกุล ขันบุตรศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
An objective of this qualitative research study, guided by Husserl phenomenological approach, was to describe lived experiences of adolescent with non-relapse amphetamine used. The key informants were female and male adolescents aged 12 – 24 years who had experience with non-relapse at least 3 months after completed the voluntary treatment program. Data were collected using the in-depth interview with tape-record and found saturated after 15 informants. Tape-recorded interviews were transcribed verbatim. Data were analyzed using Colaizzi method (1978 cited in Streubert and Carpenter, 2011).The findings revealed that lived experiences of adolescent with non-relapse amphetamine used can be categorized into 3 major themes:1) motivation to quit amphetamine including  did not wants to be the same again, quit for their own future and quit for their loved one ; 2) the protection from non-relapse amphetamine used by using self-hardiness, family support, technique gained and follow up care from the treatment system;3) method to deal with hindrances of non-relapse by using refusal strategies, dealing with craving stimulants and relapse risk situations.Findings from this study reflect pictures of experiences on lived experiences to amphetamine use among adolescents who were non-relapse after the completion of the voluntary treatment program. The informants were able to get over the hindrances of non-relapse and stayed clean by using the abilities from inner self, external support and effectively deal with non-relapse obstacles. Nurses and healthcare team can apply this research findings to develop appropriate treatment system and care plan in order to prevent amphetamine relapse in adolescent clients.